2009
DOI: 10.1007/s10620-009-0852-y
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nitric Oxide in the Expression of Renal Aquaporin 2 in a Cirrhotic Rat Model: Does an AVP-Independent Mechanism Exist for the Regulation of AQP2 Expression?

Abstract: The aquaporin (AQP) water channel is expected to play a decisive role of hyponatremia and water retention in cirrhotic patients. Despite the importance of the water channel, however, previous findings vary widely when it concerns AQP2 of the kidneys in subjects with cirrhosis. The purpose of this study was to investigate the expression of AQP2 in the distal renal tubule in cirrhosis, and the presence of the nitric oxide-AQP2 signaling pathway as a possible vasopressin-aquaporin-independent pathway. Sixty male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
2
1
Order By: Relevance
“…For example, AQP2 has been reported to be regulated by prostaglandin E 2 or nitric oxide synthetase. 30 The AQP1 level did not change after terlipressin administration in the present study, indicating that AQP1 may not be involved in the therapeutic mechanisms of terlipressin.…”
Section: Terlipressin Resolves Ascites Via Aqp2 Downregulationcontrasting
confidence: 54%
See 1 more Smart Citation
“…For example, AQP2 has been reported to be regulated by prostaglandin E 2 or nitric oxide synthetase. 30 The AQP1 level did not change after terlipressin administration in the present study, indicating that AQP1 may not be involved in the therapeutic mechanisms of terlipressin.…”
Section: Terlipressin Resolves Ascites Via Aqp2 Downregulationcontrasting
confidence: 54%
“…Terlipressin significantly increased fluid-excretion volume compared with normal control noncirrhotic group and the saline treated cirrhotic group. (B) Urine and blood osmotic pressures (mean ± SD) in the three study groups after 5 days' treatment ( a P < 0.05 compared with normal control noncirrhotic group; b P < 0.05 compared with saline-treated cirrhotic group; unpaired Student's t-test) 30 Normal …”
Section: Y-y Huang J-y Sun J-y Wang Et Al Terlipressin Resolves Asmentioning
confidence: 99%
“…Similarly, another study by Martin et al (Martin et al, 2002) showed that water deprivation induced the expression of endothelial NOS and neuronal NOS in the outer medulla as well as both the outer medulla and the papilla, respectively, which could be subsequently decreased by water loading. Other evidence further supporting the idea that NO-cGMP plays a role in water homeostatic mechanisms came from the fact that 1) VP specifically increases neuronal NOS expression levels in the renal outer medulla and papilla (Martin et al, 2002), 2) an increased expression of AQP2 within the kidneys of cirrhotic rats was found to correlate with the increasing activities of NOS (Jun et al, 2010), and 3) simultaneous disruption of all three NOS isoforms led to reduce membranous AQP2 expression associated with tubuloglomerular lesion formation, as well as marked hypotonic polyuria, polydipsia, and renal unresponsiveness to VP (Morishita et al, 2005), all of which are characteristics consistent with NDI. Thus, AQP2 expression and trafficking, which is chiefly regulated by VP, may be additionally stimulated by NO-cGMP activity.…”
Section: Factors Involved In Nitric Oxide/cgmp Pathwaymentioning
confidence: 90%